A NIR fluorescent probe based on phenazine with a large Stokes shift for the detection and imaging of endogenous H2O2 in RAW 264.7 cells. Issue 12 (5th June 2020) - Yan, Yongchao; Liu, Lingyan; Li, Chenglin; Yang, Zhicheng; Yi, Tao; Hua, Jianli
Abstract : A NIR fluorescent probe PCN-BP with a large Stokes shift was developed. It displayed fluorescence enhancement and color change after H2 O2 was added. Moreover, it was employed for the exogenous and endogenous imaging of H2 O2 in RAW 264.7 cells. Abstract : Hydrogen peroxide (H2 O2 ), one of the reactive oxygen species (ROS), plays vital roles in diverse physiological processes. Thus, herein, to improve the signal-to-noise ratio, a new near-infrared region (NIR) fluorophore (PCN ) based on reduced phenazine was developed. PCN was further designed as a "turn on" fluorescent probe (PCN-BP ) for the detection of H2 O2 by introducing p -boratebenzyl. After H2 O2 was added, the p -boratebenzyl group in PCN-BP was oxidized to p -hydroxy benzyl; it then self-departed, forming PCN, which displayed 24-fold NIR emission at 680 nm with a large Stokes shift (more than 200 nm). This probe presented an excellent linear relation with the concentration of H2 O2 and good selectivity to various ions, ROS and biothiols; thus, it can be utilized as a colorimetric and fluorescence turn-on probe. More importantly, the probe was also employed for the exogenous and endogenous imaging of H2 O2 in RAW 264.7 cells.